Self-feeding ammoniated blackstrap molases to beef heifers. - Richardson, D.; Smith, E.F.; Koch, B.A.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Forty Hereford heifer calves from the same herd were divided as equally as possible on the basis of weight and conformation into four lots of 10 animals each. Animals in all lots received all the sorghum silage they would clean up each day.
Keywords: Beef; Molasses; Rations